2017
DOI: 10.1136/bmjopen-2016-014143
|View full text |Cite
|
Sign up to set email alerts
|

Hospital variation in allogeneic transfusion and extended length of stay in primary elective hip and knee arthroplasty: a cross-sectional study

Abstract: ObjectivesOutcomes in total hip and knee arthroplasty (THA and TKA), such as allogeneic transfusions or extended length of stay (LoS), can be used to compare the performance of hospitals. However, there is much variation in these outcomes. This study aims to rank hospitals and to assess hospital differences of two outcomes in THA and TKA: allogeneic transfusions and extended LoS, and to additionally identify factors associated with these differences.DesignCross-sectional medical record review study.SettingData… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 48 publications
(24 reference statements)
2
7
0
Order By: Relevance
“…It must be noted that LOS for unilateral procedures during the same time interval in our hospital was 5.1 days, which is significantly lower than for bilateral procedures. This finding is consistent with the literature [12, 27]. The strength of the study is the prospective documentation of outcomes, alongside the low rate of attrition.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It must be noted that LOS for unilateral procedures during the same time interval in our hospital was 5.1 days, which is significantly lower than for bilateral procedures. This finding is consistent with the literature [12, 27]. The strength of the study is the prospective documentation of outcomes, alongside the low rate of attrition.…”
Section: Discussionsupporting
confidence: 91%
“…Most of the studies reported increases in homologous blood transfusion rates of 20% to 40% after sequential THA [24]. The mean LOS found in the present study was 7.6 days, which is above the average as reported in the literature [25-27]. Germany has globally one of the longest duration of stay in the hospital.…”
Section: Discussionsupporting
confidence: 41%
“…From the 20 studies reporting complication rates, the between-hospital variation was reported in 11 studies (5 MQ, 6 LQ) for THA (9,10,21,27,41,42,43,44,45,46,47), 8 studies (4 MQ, 4 LQ) for TKA (10,21,33,44,45,46,47,48) and 8 studies (1 HQ, 3 MQ, 4 LQ) for THA and TKA combined (14,15,16,32,38,47,49,50). Eight studies reported the variation more than once with different outcome definition, follow-up, and type of hospitals selected (Table 5).…”
Section: Complicationsmentioning
confidence: 99%
“…Most registries give feedback through annual reports intended to encourage quality improvement initiatives in lowwww.efortopenreviews.org 7:4 A systematic review including 33 studies and 8 arthroplasty register reports performing hospitals and learn from high-performing hospitals by adopting best practices (1,2,3,4,5,6,7,8). In addition, scientific articles are published for quality improvement purposes; for example, hospitals are benchmarked, ranked, or (statistical) methods are compared to monitor the quality of care delivered (9,10,11,12,13). The most commonly used quality indicators in this context are implant revision, readmission, and complications, as these indicators are considered reliable, actionable, and fit for purpose (14,15,16,17,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…A similar concept is referred to as ‘statistical reliability’ by others [13]. This concept has been implemented for both diagnostic and process indicators [14], as well as for outcome indicators in different fields [1518].…”
Section: Introductionmentioning
confidence: 99%